Loss of the inactive myotubularin-related phosphatase Mtmr13 leads to a Charcot–Marie–Tooth 4B2-like peripheral neuropathy in mice - Robinson, Fred L. (National Academy of Sciences, 2008)
Charcot–Marie–Tooth disease type 4B (CMT4B) is a severe, demyelinating peripheral neuropathy characterized by slowed nerve conduction velocity, axon loss, and distinctive myelin outfolding and infolding. CMT4B is caused by recessive mutations in either myotubularin-related protein 2 (MTMR2; CMT4B1) or MTMR13 (CMT4B2). Myotubularins are phosphoinositide (PI) 3-phosphatases that dephosphorylate phosphatidylinositol 3-phosphate (PtdIns3P) and PtdIns(3,5)P(2), two phosphoinositides that regulate endosomal–lysosomal membrane traffic. Interestingly, nearly half of the metazoan myotubularins are predicted to be catalytically inactive. Both active and inactive myotubularins have essential functions in mammals and in Caenorhabditis elegans. MTMR2 and MTMR13 are active and inactive PI 3-phosphatases, respectively, and the two proteins have been shown to directly associate, although the functional significance of this association is not well understood. To establish a mouse model of CMT4B2, we disrupted the Mtmr13 gene. Mtmr13-deficient mice develop a peripheral neuropathy characterized by reduced nerve conduction velocity and myelin outfoldings and infoldings. Dysmyelination is evident in Mtmr13-deficient nerves at 14 days and worsens throughout life. Thus, loss of Mtmr13 in mice leads to a peripheral neuropathy with many of the key features of CMT4B2. Although myelin outfoldings and infoldings occur most frequently at the paranode, our morphological analyses indicate that the ultrastructure of the node of Ranvier and paranode is intact in Mtmr13-deficient nerve fibers. We also found that Mtmr2 levels are decreased by ≈50% in Mtmr13-deficient sciatic nerves, suggesting a mode of Mtmr2 regulation. Mtmr13-deficient mice will be an essential tool for studying how the loss of MTMR13 leads to CMT4B2.